2021
DOI: 10.3329/brj.v24i2.53452
|View full text |Cite
|
Sign up to set email alerts
|

Soil Health as Influenced by Fertilizer Management in Rice Based Cropping System

Abstract: Nutrient management influences soil health and crop productivity. Sustained crop production re-quires specific nutrient management options after a certain period. The objectives of this investigation were to examine the effects of inorganic and organic fertilization on yields and soil carbon budget under rice based cropping patterns in Bangladesh. The research data and informationhave been gen-erated based on previouslypublished, unpublished sources and own concept.Omission of K or im-balanced K are more influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Malik and Chauhan [31] stated that integrated treatment (organic and inorganic) gave the higher values for soil N, P and K contents whereas the inorganic treatment gave significantly lower values for those nutrients. At the present research location (BAU farm), Bilkis [32] and Haque [33] also observed increased OM, N, P and S contents of soil after two crop cycles due to integrated use of manure and fertilizers. Rekaby et al [11] reported a higher availability of nutrients in Egypt soils after organic amendment (biochar, humic acid and compost).…”
Section: Effects Of Amended Compost On Changes In Soil Propertiesmentioning
confidence: 56%
“…Malik and Chauhan [31] stated that integrated treatment (organic and inorganic) gave the higher values for soil N, P and K contents whereas the inorganic treatment gave significantly lower values for those nutrients. At the present research location (BAU farm), Bilkis [32] and Haque [33] also observed increased OM, N, P and S contents of soil after two crop cycles due to integrated use of manure and fertilizers. Rekaby et al [11] reported a higher availability of nutrients in Egypt soils after organic amendment (biochar, humic acid and compost).…”
Section: Effects Of Amended Compost On Changes In Soil Propertiesmentioning
confidence: 56%
“…It may cause a 20 to 50% decrease in efficiency. Haque et al (2021) also reported that paddy grain yields are significantly higher (31 to 45%) under organic amendments chemical fertilizer treatment. Lenin et al (2021) noticed that applying 2.5 t ha -1 compost without chemicals can reduce yield by 23%.…”
Section: Organic and Farm Waste Applicationmentioning
confidence: 91%
“…Copyright © 2022 Universitas Sebelas Maret management practices, severe weed problems in high rainfall areas and poor crop and land management practices adopted in the dry areas, such as rainfed paddy fields. Haque et al (2021) explained that using only chemical fertilizers as inputs could not increase paddy yields. Moreover, most fertilization in rainfed paddy fields does not follow the government recommendations and this is estimated to affect fertilization efficiency in the soil.…”
Section: Organic and Farm Waste Applicationmentioning
confidence: 99%